The brownout murders - Jackson, Luke C.; Jackson, Kelley (Scribe, 2025)
The year is 1942, the place Melbourne. A brownout is in effect to dim the night-time lights of the city, and thousands of American GIs are based in Royal Park. As the latter make plans to defend the Pacific, the women of Australia have stepped up to support the war effort at home. Beatrice is doing her part. She's enlisted as an air raid warden, preparing the city ahead of a possible Japanese attack. Her sister June is an operator at the telephone exchange, while her other sister, Lizzie, works as a shopgirl by day and parties with the Americans by night. But the times are about to change again, and the three sisters will have to navigate the consequences of a new threat as a series of grisly murders are committed in the eerie half-light of the brownout. Inspired by true events, The Brownout Murders tells a story of fear, fortitude, and social change -- and how the independence of all women is too often set against the violence of a single man.